TANGGUNG JAWAB PEMERINTAH DAERAH TERHADAP PEMELIHARAAN JALAN DI KABUPATEN ENREKANG (PRESPEKTIF SIYASAH SYAR’IYYAH) - Irwan, Rezky Amaliyah (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2024)
The subject of this research is how the responsibility of the local government towards road maintenance in Enrekang Regency (Prespekti Siyasah Syar’iyyah). The purpose of this study was to determine the role of local governments in the implementation of road maintenance, the factors that became obstacles for local governments in the implementation of road maintenance and how the siyasah syar’iyyah perspective on the responsibility of local governments for road maintenance in Enrekang Regency. This type of research is a field research using a syar’i normative approach and a normative juridical approach. This research was conducted by collecting data obtained from a number of informants and conducting observations to observe social phenomena related to the research. The results of this study indicate that the local government of Enrekang Regency has made various efforts in road maintenance by carrying out the planning, budgeting, and implementation stages accompanied by supervision, and maintenance in the form of routine, periodic road maintenance and road binding The inhibiting factors in road maintenance in Enrekang Regency are unsupported road locations such as inadequate land, lack of budget and lack of community participation. The local government in carrying out road maintenance as an obligation and authority has not been fully in accordance with the principles of Siyasah Syar’iyyah such as in terms of planning, budget allocation, and implementation and in carrying out the duties and responsibilities of the local government of Enrekang Regency it is still not fully fulfilled because there are still a lot of damage. roads, and the lack of complementary road facilities, both axis roads and regional roads in various areas in Enrekang Regency.